Lumberjanes: somewhere that's green ebook - McGuire, Seanan (Lumberjanes (2014)., 2019)
When Jo, April, Mal, Molly, and Ripley stumble upon several muddy, spiky, cactus kittens in the woods, they take on the sacred mission of bringing the kittens back to their home. However, when they reach the garden menageries and its Dryad tender, they find that there is a deeper problem at the heart of the garden—and the Roanokes are the only ones who can help! Writer Seanan McGuire (Spider-Gwen) and artist Alexa Bosy team up for an entirely new Lumberjanes story! PLUS an all-new short story from Mariana Costa (Peritale)!